2018
DOI: 10.4103/aja.aja_28_17
|View full text |Cite
|
Sign up to set email alerts
|

Trials of testosterone replacement reporting cardiovascular adverse events

Abstract: The numbers of testosterone prescriptions written have increased several-fold worldwide, but the incidence of pathological hypogonadism due to hypothalamic, pituitary, and testicular disease has remained unchanged. Most of these prescriptions are being dispensed to middle-aged and older men who have experienced age-related decline in serum testosterone levels; a subset of the population in which benefits of testosterone replacement is at best, modest. Recently, some randomized controlled trials have reported i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 89 publications
0
6
0
Order By: Relevance
“…Higher dose of testosterone (100 µg/kg) not only did not mitigate renal injury but also increased both IL-10 and TNF-α levels. A recent review shared our point of view [ 7 ]. They pointed out that the number of testosterone prescriptions in the United States has increased in recent years.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Higher dose of testosterone (100 µg/kg) not only did not mitigate renal injury but also increased both IL-10 and TNF-α levels. A recent review shared our point of view [ 7 ]. They pointed out that the number of testosterone prescriptions in the United States has increased in recent years.…”
Section: Discussionmentioning
confidence: 98%
“…For example, several studies indicated that testosterone protects against atherosclerosis and cardiometabolic syndrome [ 3 , 4 , 5 ]. On the contrary, some studies hold the opposite view that testosterone and its derivatives exert toxic effects on the cardiovascular system [ 6 , 7 ]. Animal experiments confirmed the mixed side effects of testosterone.…”
Section: Introductionmentioning
confidence: 99%
“…There is conflicting information regarding the role of the sex hormones in regulating cell death in cardiac tissue, and therefore, indicated a need for further research in this area ( Djouadi et al, 1998 ; Morris and Channer, 2012 ; Hsieh et al, 2015 ; Wang F. et al, 2015 ; Gagliano-Juca and Basaria, 2018 ; Jones and Kelly, 2018 ). Cell death pathways, including apoptosis, autophagy, necrosis, and pyroptosis, have been implicated in inducing cell death in CVD among various cell types within the heart including cardiomyocytes, endothelial cells, and monocytes/macrophages ( Subramanian and Shaha, 2007 ; Wang F. et al, 2010 ; Chen et al, 2014 ; Feng et al, 2017 ; Amgalan et al, 2020 ; Di Florio et al, 2020 ).…”
Section: Cell Deathmentioning
confidence: 99%
“… 4 As they note, some randomized controlled trials have reported increased cardiovascular events in older men with prevalent cardiovascular disease. 5 Although the United States Testosterone Trial, the largest placebo-controlled trial of testosterone therapy in older men to date, did not demonstrate increased cardiovascular events after one year of testosterone replacement therapy compared to placebo, there was an increased risk of progression of non-calcified coronary plaque. 6 7 …”
mentioning
confidence: 99%